2014
DOI: 10.1088/0004-637x/796/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Are Dusty Galaxies Blue? Insights on Uv Attenuation From Dust-Selected Galaxies

Abstract: Galaxies' rest-frame ultraviolet (UV) properties are often used to directly infer the degree to which dust obscuration affects the measurement of star formation rates. While much recent work has focused on calibrating dust attenuation in galaxies selected at rest-frame ultraviolet wavelengths, locally and at high-z, here we investigate attenuation in dusty, star-forming galaxies (DSFGs) selected at farinfrared wavelengths. By combining multiwavelength coverage across 0.15-500 µm in the COSMOS field, in particu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
286
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 168 publications
(316 citation statements)
references
References 147 publications
27
286
3
Order By: Relevance
“…However, UV radiation is able to leak through small openings in the dust cocoon. These leakages may be associated with short and extreme bursts of star formation that have been proposed to explain the intrinsically blue rest-frame UV slope observed in dusty, star-forming galaxies (SFR>50 M e yr −1 ) up to z∼5 (e.g., Casey et al 2014). A similar scenario was also proposed by Decarli et al (2012) to explain the lack of extended Lyα emission from the host galaxy of the two highly star-forming z>6 QSOs: SDSSJ1030+0524 and SDSSJ1148+5251 (see also Mechtley et al 2012).…”
Section: The Host Galaxy Of J0305−3150mentioning
confidence: 97%
“…However, UV radiation is able to leak through small openings in the dust cocoon. These leakages may be associated with short and extreme bursts of star formation that have been proposed to explain the intrinsically blue rest-frame UV slope observed in dusty, star-forming galaxies (SFR>50 M e yr −1 ) up to z∼5 (e.g., Casey et al 2014). A similar scenario was also proposed by Decarli et al (2012) to explain the lack of extended Lyα emission from the host galaxy of the two highly star-forming z>6 QSOs: SDSSJ1030+0524 and SDSSJ1148+5251 (see also Mechtley et al 2012).…”
Section: The Host Galaxy Of J0305−3150mentioning
confidence: 97%
“…11 It is therefore a valid tool to study the ISM column density of galaxies (Meurer et al 1999;Kong et al 2004;Casey et al 2014). Furthermore, β is the only estimate of the dust content available for the vast majority of galaxies at z>3 due to the relative insensitivity of contemporary optical and IR surveys.…”
Section: Measurements and Simulationsmentioning
confidence: 99%
“…There are many other works that have explored variations in the IRX -β relation and their physical cause in local galaxies (e.g., Burgarella, Buat & Iglesias-Páramo 2005;Seibert et al 2005;Cortese et al 2006;Gil de Paz et al 2007;Johnson et al 2007;Panuzzo et al 2007;Cortese et al 2008;Siana et al 2008;Boquien et al 2009;Muñoz-Mateos et al 2009;Wijesinghe et al 2011;Boquien et al 2012;Ye et al 2016). High-redshift observations have demonstrated that dusty star-forming galaxies (DSFGs) have bluer UV continuum slopes for a given IRX (increasingly deviating from the Meurer et al relation as a function of IR luminosity, e.g., Oteo et al 2013;Casey et al 2014;Bourne et al 2017). High-redshift Lyman Break Galaxies are observed to have redder UV continuum slopes β for a given IRX value, more consistent with a Small Magellanic Cloud (SMC) or Large Magellanic Cloud (LMC) attenuation curve than the canonical Meurer, Heckman & Calzetti (1999) relation (e.g., Capak et al 2015;Bouwens et al 2016;Koprowski et al 2016;Pope et al 2017;Smit et al 2017).…”
Section: Introductionmentioning
confidence: 99%